Pesantren Darussalam Al-Amin : Sekolah Pendidikan Agama - Sisilia Nehemia; Nur Adila; Arismunandar; Ahlun Ansar; Nurlela (Pendidikan Al-Gafari, 2024)
This study aims to describe the educational model at the Darussalam Al-Amin Makassar Islamic Boarding School and assess its role and management in supporting religious education for students. The research uses a descriptive qualitative approach, data is obtained through observation and in-depth interviews with pesantren managers. The results of the study show that the Darussalam Al-Amin Islamic Boarding School integrates the traditional curriculum, such as the teaching of the yellow book, with modern methods that encourage the cognitive, affective, and psychomotor skills of students. The organizational structure led by Kyai H. Faiz emphasizes leadership based on Islamic values, while the flagship learning program includes tahfidz Al-Qur'an and fiqh education. In addition, Islamic boarding schools provide counseling services for students and involve parents in the educational process, so that holistic support is created in the development of students' character and skills. The Darussalam Al-Amin Islamic Boarding School is one example of non-formal education in the category of boarding boarding schools. Darussalam Al-Amin Islamic Boarding School plays a significant role in the non-formal education system in Indonesia, with a comprehensive approach that integrates religious teaching through the yellow books and various other disciplines.